2023
DOI: 10.3390/jcm13010075
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of the Rho-Kinase Inhibitor (Ripasudil) in Bleb Needling after Trabeculectomy: A Prospective Multicenter Study

Yu Mizuno,
Kaori Komatsu,
Kana Tokumo
et al.

Abstract: Ripasudil, a rho-associated protein kinase inhibitor ophthalmic solution, shows a protective effect in preventing excessive scarring in vitro. This study aims to evaluate the safety and efficacy of ripasudil for glaucoma patients submitted to the needling procedure. In this prospective, multicenter, single-arm study, we included 20 eyes of 20 patients with glaucoma who underwent the needling procedure without antimetabolites. All patients administered ripasudil after needling for three months. The primary endp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…The in vivo animal model studies also revealed similar findings. They suggested that ROCK inhibitors have therapeutic potential in reducing scar formation after glaucoma filtration surgeries by inhibiting the transdifferentiation of fibroblasts into myofibroblasts and extracellular matrix deposition in rabbit and rat models [ 20 , 38 , 39 , 40 ]. In real-world clinical practice, further research is needed to determine if ROCK inhibitors exhibit similar anti-fibrosis properties.…”
Section: Rho/rho Kinase Pathway In the Role Of Glaucomamentioning
confidence: 99%
“…The in vivo animal model studies also revealed similar findings. They suggested that ROCK inhibitors have therapeutic potential in reducing scar formation after glaucoma filtration surgeries by inhibiting the transdifferentiation of fibroblasts into myofibroblasts and extracellular matrix deposition in rabbit and rat models [ 20 , 38 , 39 , 40 ]. In real-world clinical practice, further research is needed to determine if ROCK inhibitors exhibit similar anti-fibrosis properties.…”
Section: Rho/rho Kinase Pathway In the Role Of Glaucomamentioning
confidence: 99%